Sulfide-based solid electrolyte compound
Patent Information
- Application Number
- CN202580016201.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-24
- Filing Date
- 2025-09-12
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]然而,固体电解质的离子电导率低于液体电解质,且存在在电池内部因分解反应而容易劣化的问题
根据本说明书,通过在硫银锗矿型硫化物系固体电解质化合物的表面中的至少一部分混合LiX晶相而改善大气稳定性和电化学稳定性,并且包括该化合物的锂二次电池即使在长期使用时也不会发生过电压增加,从而能够呈现稳定的循环行为。
Smart Images

Figure CN123023162A_ABST
Abstract
Description
Technical Field
[0001] This specification relates to sulfide-based solid electrolyte compounds, solid electrolyte membranes including such compounds, and lithium secondary batteries. More specifically, this specification relates to a method for improving the atmospheric and electrochemical stability of sulfide-based solid electrolytes having an Argyrodite-type crystal structure. It also relates to a sulfide-based solid electrolyte compound, a solid electrolyte membrane, and a lithium secondary battery including such a compound, which can improve stability by forming a LiX crystal phase in at least a portion of the surface of the sulfide-based solid electrolyte compound having an Argyrodite-type crystal structure to suppress the decomposition reaction of the solid electrolyte. Background Technology
[0002] Batteries use materials capable of electrochemical reactions at the positive and negative electrodes to store electrical energy. As a representative example of such batteries, there are lithium secondary batteries that store electrical energy through the difference in chemical potential during the insertion / extraction of lithium ions at the positive and negative electrodes.
[0003] The aforementioned lithium secondary battery is prepared by using materials capable of reversible lithium-ion insertion / extraction as positive and negative electrode active materials, and filling the space between the positive and negative electrodes with organic or polymer electrolytes.
[0004] However, these organic or polymer electrolytes typically use flammable organic solvents. Therefore, when abnormally high temperatures occur due to internal or external factors affecting the lithium secondary battery, there is a possibility of fire or explosion caused by the electrolyte.
[0005] Due to these safety concerns, solid-state batteries, which utilize solid electrolytes, have gained attention as an alternative to liquid batteries. Solid-state batteries offer high stability and are expected to be commercialized as a next-generation battery with high energy density. Furthermore, if a solid electrolyte is introduced as a membrane structure, it can replace the separation membrane essential in liquid batteries.
[0006] Sulfide-based solid electrolytes are known as solid electrolytes used in lithium-ion batteries. Various crystal structures of sulfide-based solid electrolytes are known, including the Argyrodite type.
[0007] However, solid electrolytes have lower ionic conductivity than liquid electrolytes and are prone to degradation due to decomposition reactions inside the battery. Furthermore, sulfide-based solid electrolytes can react with atmospheric moisture and / or oxygen to produce hydrogen sulfide.
[0008] Therefore, there is a need to develop a novel compound that can improve the atmospheric and electrochemical stability of sulfide-based solid electrolyte compounds while also exhibiting high ionic conductivity. Summary of the Invention
[0009] Technical issues According to this specification, one object is to provide a sulfide-based solid electrolyte compound that, by leaving at least a portion of the surface of the sulfide-based solid electrolyte compound with a residual LiX crystal phase, inhibits the reaction between the solid electrolyte and water and / or oxygen, while improving ionic conductivity, thereby achieving excellent atmospheric stability and electrochemical stability.
[0010] Furthermore, one object of this specification is to provide a solid electrolyte membrane and a lithium secondary battery using a sulfide-based solid electrolyte compound as defined herein.
[0011] The purpose of this specification is not limited to those stated above. Other purposes and advantages not mentioned herein will be understood through the following description and through the embodiments described herein. Furthermore, it will be readily understood that the purposes and advantages of this invention can be achieved by the means and combinations thereof described in the claims.
[0012] Technical solution According to one aspect of this specification, a sulfide-based solid electrolyte compound for lithium-ion batteries is provided, comprising a crystal phase with an Argyrodite-type crystal structure, and at least a portion thereof comprising a LiX crystal phase, wherein X is at least one selected from the group consisting of F, Cl, Br and I.
[0013] The peak intensity ratio I(200) / I(220) of the (220) facet of the sulfosilver germanite-type crystal structure and the (200) facet of the LiX crystal phase can be less than 0.30.
[0014] Here, in the crystal phase of the sulfide-germanium ore-type crystal structure, the molar ratio of lithium (Li) to phosphorus (P) can exceed 5.7 and be less than 6.15.
[0015] Furthermore, in the crystal phase of the sulfogermanium ore-type crystal structure, the molar ratio of sulfur (S) to phosphorus (P) can be 4.00 to 6.00.
[0016] On the other hand, the crystal phase of the sulfosilver germanite-type crystal structure may include two or more halogen elements.
[0017] Here, in the crystal phase of the sulfide-germanium ore-type crystal structure, the molar ratio of halogen (X) and phosphorus (P) elements, X / P, can be 1.00 to 2.00.
[0018] Furthermore, in the crystal phase of the sulfide-germanium ore type crystal structure, the molar ratio (Li+X) / P of the sum of lithium (Li) and halogen (X) elements relative to phosphorus (P) can exceed 7.00.
[0019] In one embodiment, the crystal phase of the sulfide-germanium ore-type crystal structure can be represented by the following chemical formula 1: [Chemical Formula 1] Li 7-x+y PS 6-x Cl x Br y In the aforementioned chemical formula 1, 1 ≤ x ≤ 1.6, 0 <y≤0.4。
[0020] Furthermore, the peak intensity ratio I(200) / I(220) of the (220) facet of the sulfosilver germanite-type crystal structure and the (200) facet of the LiCl crystal phase can be less than 0.30.
[0021] In another embodiment, the lattice constant of the crystal phase of the silver-germanium sulfide crystal structure may exceed 9.439 Å and be less than 9.645 Å.
[0022] On the other hand, the sulfide-based solid electrolyte compound for lithium-ion batteries can be prepared by mixing lithium sulfide (Li₂S) powder, phosphorus pentasulfide (P₂S₅) powder, lithium chloride (LiCl) powder, and lithium bromide (LiBr) powder, and then applying the mixture at 350°C under an inert atmosphere. Firing at 600°C, or at 350°C in an atmosphere including hydrogen sulfide gas. It is obtained by firing at 650℃.
[0023] Furthermore, the content of the lithium chloride (LiCl) powder may be higher than the content of the lithium bromide (LiBr) powder.
[0024] According to another aspect, a solid electrolyte membrane comprising the sulfide-based solid electrolyte compound is provided.
[0025] According to another aspect, a lithium secondary battery having the aforementioned solid electrolyte membrane is provided.
[0026] Beneficial effects According to this specification, atmospheric stability and electrochemical stability are improved by mixing at least a portion of the LiX crystalline phase into the surface of a sulfide-based solid electrolyte compound of silver-germanium sulfide type, and lithium secondary batteries including this compound do not experience overvoltage increases even during long-term use, thereby exhibiting stable cycling behavior.
[0027] In addition to the effects described above, the specific effects of the present invention will be described below while explaining the specific matters for carrying out the invention. Attached Figure Description
[0028] Figure 1 The XRD analysis results are for a sulfide compound according to an example of this specification; Figure 2 The amount of hydrogen sulfide produced for a sulfide-based compound according to an example of this specification; Figure 3 The results are an evaluation of the electrochemical characteristics of a symmetrical battery comprising a sulfide-based compound, as exemplified in this specification. Detailed Implementation
[0029] To facilitate understanding of this specification, specific terms are defined herein for convenience. Unless otherwise defined herein, scientific and technical terms used in this specification shall have the meanings commonly understood by one of ordinary skill in the art. Furthermore, unless the context specifically indicates otherwise, the singular form of a term shall also include its plural form, and the plural form of a term shall also be understood to include its singular form.
[0030] Sulfide solid electrolyte compounds According to one aspect of this specification, the sulfide-based solid electrolyte compound may include a crystal phase with an Argyrodite-type crystal structure, and at least a portion of its surface may include a LiX crystal phase.
[0031] The sulfide-based solid electrolyte compound has lithium-ion conductivity and may have a mixed phase including a sulfide-germanium ore-type crystal structure and a LiX crystal phase.
[0032] The argyrogermanium sulfide crystal structure refers to the same structure as argyrogermanium sulfide (Ag8GeS6), a silver-germanium-sulfur mineral. The argyrogermanium sulfide crystal structure can exhibit both orthorhombic (Pna21) and cubic (F-43m) phases, with the cubic phase exhibiting higher lithium-ion conductivity. Typically, the argyrogermanium sulfide crystal structure exhibits a cubic phase with excellent lithium-ion conductivity at high temperatures and an orthorhombic phase at low temperatures.
[0033] For example, Li7PS6 and Li6PS5X (where X is at least one of Cl, Br, and I) are known as lithium-ion conductive solid electrolyte compounds with a sulfogermanium ore-type crystal structure.
[0034] However, the argyrocerite-type crystal structure is sensitive to air and humidity, which can easily lead to performance degradation. Furthermore, compounds with the argyrocerite-type crystal structure may easily decompose when reacting with lithium due to their narrow potential window.
[0035] Conversely, the sulfide-based solid electrolyte compound comprises a LiX phase with a relatively broad and stable potential window, thereby suppressing decomposition reactions of the compound at the interface. Therefore, secondary batteries using the sulfide-based solid electrolyte compound exhibit stable cycling behavior.
[0036] The LiX phase can be formed by adding an excess of LiX (X being at least one of Cl, Br, and I) during the manufacture of the sulfide-based solid electrolyte compound, thus leaving LiX residue. In this case, LiX can also be formed by using two or more compounds, rather than just one, to leave one of them residue.
[0037] Here, excess can mean that the sum of the molar ratio of lithium (Li) and phosphorus (P) Li / P and the molar ratio of halogen (X) and phosphorus (P) X / P, (Li+X) / P, exceeds 7.
[0038] The peak intensity ratio I(200) / I(220) of the (220) plane of the sulfogermanium-type crystal structure and the (200) plane of the LiX crystal phase can be less than 0.30, for example, it can be 0.30, 0.29, 0.28, 0.27, 0.26, 0.25, 0.24, 0.23, 0.22, 0.21, 0.20, 0.19, 0.18, 0.17, 0.16, 0.15, 0.14, 0.13, 0.12, 0.11, 0.10, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02, 0.01 or a range between two of these values, but is not limited thereto.
[0039] In XRD analysis using a Cu target, the (220) plane appears at approximately 2θ = 25.2, and the (200) plane appears at approximately 2θ = 34.9. If the peak intensity ratio between the silver sulfide-germanium ore phase and the LiX phase meets the aforementioned range, the problem of decreased ionic conductivity or atmospheric stability of the solid electrolyte can be prevented.
[0040] Here, in the crystal phase of the sulfide-germanium-type crystal structure, the molar ratio of lithium (Li) to phosphorus (P), Li / P, can exceed 5.7 and be less than 6.15, for example, it can be 5.71, 5.72, 5.73, 5.74, 5.75, 5.76, 5.77, 5.78, 5.79, 5.80, 5.81, 5.82, 5.83, 5.84, 5.85, 5.86, 5.87, 5.88, 5. 89, 5.90, 5.91, 5.92, 5.93, 5.94, 5.95, 5.96, 5.97, 5.98, 5.99, 6.00, 6.01, 6.02, 6.03, 6.04, 6.05, 6.06, 6.07, 6.08, 6.09, 6.10, 6.11, 6.12, 6.13, 6.14, 6.15, or a range between two of these values, but not limited to these.
[0041] If the Li / P value deviates from the specified range, the arrangement and distribution ratio of lithium ions within the compound changes, which may lead to a decrease in ionic conductivity.
[0042] Furthermore, in the crystal phase of the sulfide-germanium-type crystal structure, the molar ratio of sulfur (S) to phosphorus (P), S / P, can be 4.00~6.00, for example 4.00, 4.05, 4.10, 4.15, 4.20, 4.25, 4.30, 4.35, 4.40, 4.45, 4.50, 4.55, 4.60, 4.65, 4.70, 4.75, 4.80, 4.85, 4.90, 4.95, 5.00, 5.05, 5.10, 5.15, 5.20, 5.25, 5.30, 5.35, 5.40, 5.45, 5.50, 5.55, 5.60, 5.65, 5.70, 5.75, 5.80, 5.85, 5.90, 5.95, 6.00, or a range between two of these values, but not limited to these.
[0043] If the S / P value meets the specified range, the chemical stability and high ionic conductivity of the compound can be ensured in a balanced manner.
[0044] In the sulfide-germanium ore type crystal structure, if sulfur is replaced with halide anions, the cubic crystal system can be stabilized, thus allowing it to have a cubic crystal system structure at room temperature.
[0045] The substituted halogen element creates a vacancy at the Li site inside the unit cell of silver-germanium sulfide, thereby reducing the activation energy and forming a new lithium-ion conduction pathway, which in turn improves the lithium-ion conductivity.
[0046] On the other hand, the crystal phase of the sulfogermanite-type crystal structure may include two or more halogen elements. Halogen elements include F, Cl, Br, and I, but in compounds with a sulfogermanite-type crystal structure, Cl, Br, and I are commonly used.
[0047] Here, in the crystal phase of the sulfide-germanium type crystal structure, the molar ratio of halogen (X) to phosphorus (P), X / P, can be 1.00 to 2.00, for example, 1.00, 1.02, 1.04, 1.06, 1.08, 1.10, 1.12, 1.14, 1.16, 1.18, 1.20, 1.22, 1.24, 1.26, 1.28, 1.30, 1.32, 1.34, 1.36, 1.38, 1.40, 1.42. The values may be 1.44, 1.46, 1.48, 1.50, 1.52, 1.54, 1.56, 1.58, 1.60, 1.62, 1.64, 1.66, 1.68, 1.70, 1.72, 1.74, 1.76, 1.78, 1.80, 1.82, 1.84, 1.86, 1.88, 1.90, 1.92, 1.94, 1.96, 1.98, 2.00, or a range between two of these values, but are not limited to these.
[0048] In one example, in the crystal phase of the sulfide-germanium-type crystal structure, the molar ratio (Li+X) / P of the total lithium (Li) and halogen (X) elements relative to phosphorus (P) can exceed 7.00, for example 7.01, 7.02, 7.03, 7.04, 7.05, 7.06, 7.07, 7.08, 7.09, 7.10, 7.11, 7.12, 7.13, 7.14, 7.15, 7.16, 7.17, 7.18, 7.19, 7.2. 0, 7.21, 7.22, 7.23, 7.24, 7.25, 7.26, 7.27, 7.28, 7.29, 7.30, 7.31, 7.32, 7.33, 7.34, 7.35, 7.36, 7.37, 7.38, 7.39, 7.40, 7.41, 7.42, 7.43, 7.44, 7.45, 7.46, 7.47, 7.48, 7.49, 7.50, or a range between two of these values, but not limited to these.
[0049] Here, if the halogen (X) element includes Cl and Br, the content of Cl may be higher than the content of Br.
[0050] Further, the content of Br may be 0.05 to 0.4 moles, for example, 0.05 mole, 0.06 mole, 0.07 mole, 0.08 mole, 0.09 mole, 0.1 mole, 0.11 mole, 0.12 mole, 0.13 mole, 0.14 mole, 0.15 mole, 0.16 mole, 0.17 mole, 0.18 mole, 0.19 mole, 0.2 mole, 0.21 mole, 0.22 mole, 0.23 mole, 0.24 mole, 0.25 mole, 0.26 mole, 0.27 mole, 0.28 mole, 0.29 mole, 0.3 mole, 0.31 mole, 0.32 mole, 0.33 mole, 0.34 mole, 0.35 mole, 0.36 mole, 0.37 mole, 0.38 mole, 0.39 mole, 0.4 mole, or a range between any two of these values, based on 1 mole of the phosphorus (P) element, but is not limited thereto.
[0051] In one embodiment, the crystal phase of the argyrodite-type crystal structure may be represented by the following Chemical Formula 1: [Chemical Formula 1] Li 7-x+y PS 6-x Cl x Br y In the Chemical Formula 1, 1≤x≤1.6, 0<y≤0.4. For example, the x may be 1, 1.02, 1.04, 1.06, 1.08, 1.1, 1.12, 1.14, 1.16, 1.18, 1.2, 1.22, 1.24, 1.26, 1.28, 1.3, 1.32, 1.34, 1.36, 1.38, 1.4, 1.42, 1.44, 1.46, 1.48, 1.5, 1.52, 1.54, 1.56, 1.58, 1.6, or a value between any two of these values, and the y may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, or a value between any two of these values, but the present disclosure is not limited thereto.
[0052] Furthermore, the peak intensity ratio I(200) / I(220) of the (220) facet of the sulfogermanite-type crystal structure phase, which includes Cl and Br and has a Cl content higher than Br, and the (200) facet of the LiCl crystal phase, can be less than 0.30, for example, 0.30, 0.29, 0.28, 0.27, 0.26, 0.25, 0.24, 0.23, 0.22, 0.21, 0.20, 0.19, 0.18, 0.17, 0.16, 0.15, 0.14, 0.13, 0.12, 0.11, 0.10, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02, 0.01, or a range between two of these values, but is not limited thereto.
[0053] Thus, if the molar ratio of Cl to Br and the value of I(200) / I(220) satisfy the aforementioned range, at least a portion of LiCl will remain on the surface of the compound, thereby inhibiting the decomposition reaction of the solid electrolyte at the interface and reducing the generation of hydrogen sulfide caused by substances present in the atmosphere. Furthermore, it maintains high ionic conductivity even after atmospheric contact.
[0054] In another embodiment, the lattice constant of the crystal phase of the argyrocerite-type crystal structure can exceed 9.439 Å and be less than 9.645 Å, for example, 9.440 Å, 9.445 Å, 9.450 Å, 9.455 Å, 9.460 Å, 9.465 Å, 9.470 Å, 9.475 Å, 9.480 Å, 9.485 Å, 9.490 Å, 9.495 Å, 9.500 Å, 9.505 Å, 9.510 Å, 9.515 Å, 9.520 Å, 9.525 Å, 9.530 Å, etc. Å, 9.535Å, 9.540Å, 9.545Å, 9.550Å, 9.555Å, 9.560Å, 9.565Å, 9.570Å, 9.575Å, 9.580Å, 9.585Å, 9.590Å, 9.595Å, 9.600Å, 9.605Å, 9.610Å, 9.615Å, 9.620Å, 9.625Å, 9.630Å, 9.635Å, 9.640Å, 9.644Å, or a range between two of these values, but not limited to these.
[0055] Compounds including sulfogermanium-type crystal phases that satisfy the range described above can be compounds in which halogen anions are substituted at the position of sulfur anions to form lithium conduction pathways.
[0056] On the other hand, the sulfide-based solid electrolyte compound for lithium-ion batteries can be prepared by mixing lithium sulfide (Li₂S) powder, phosphorus pentasulfide (P₂S₅) powder, lithium chloride (LiCl) powder, and lithium bromide (LiBr) powder, and then applying the mixture at 350°C under an inert atmosphere. 600℃, for example 350℃, 355℃, 360℃, 365℃, 370℃, 375℃, 380℃, 385℃, 390℃, 395℃, 400℃, 405℃, 410℃, 415℃, 420℃, 425℃, 430℃, 435℃, 440℃, 445℃, 450℃, 455℃, 460℃, 465℃, 470℃, 475℃, 480℃, 485℃, 4 Firing at temperatures ranging from 90°C, 495°C, 500°C, 505°C, 510°C, 515°C, 520°C, 525°C, 530°C, 535°C, 540°C, 545°C, 550°C, 555°C, 560°C, 565°C, 570°C, 575°C, 580°C, 585°C, 590°C, 595°C, 600°C, or between two of these values, or at 350°C in an atmosphere including hydrogen sulfide gas. 650℃, for example 350℃, 355℃, 360℃, 365℃, 370℃, 375℃, 380℃, 385℃, 390℃, 395℃, 400℃, 405℃, 410℃, 415℃, 420℃, 425℃, 430℃, 435℃, 440℃, 445℃, 450℃, 455℃, 460℃, 465℃, 470℃, 475℃, 480℃, 485℃, 490℃, 495℃, 500℃, 505℃ It is obtained by firing at temperatures ranging from 510℃, 515℃, 520℃, 525℃, 530℃, 535℃, 540℃, 545℃, 550℃, 555℃, 560℃, 565℃, 570℃, 575℃, 580℃, 585℃, 590℃, 595℃, 600℃, 605℃, 610℃, 615℃, 620℃, 625℃, 630℃, 635℃, 640℃, 645℃, 650℃, or between two of these values.
[0057] Here, the components can be calculated and mixed according to stoichiometry to have the composition of the chemical formula 1.
[0058] Furthermore, the firing temperature and atmosphere can be applied differently depending on the desired composition.
[0059] Furthermore, the content of the lithium chloride (LiCl) powder can be higher than the content of the lithium bromide (LiBr) powder. This form of compound exhibits both high ionic conductivity and excellent stability.
[0060] On the other hand, the lithium chloride (LiCl) phase can remain on the surface of the sulfide-based solid electrolyte compound by adding an excess of the lithium bromide powder. For example, the lithium bromide powder can be added in such a way that the total moles of lithium (Li), chlorine (Cl), and bromine (Br) divided by the moles of phosphorus (P) exceeds 7.
[0061] solid electrolyte membrane According to another aspect, a solid electrolyte membrane comprising the sulfide-based solid electrolyte compound is provided.
[0062] Here, solid electrolyte membrane can mean an electrolyte membrane formed from sulfide-based solid electrolyte compounds that are a type of solid material capable of ion conduction.
[0063] Solid electrolyte membranes can be manufactured according to conventional methods known in the art, for example by pressing powdered sulfide-based solid electrolyte compounds into the desired shape.
[0064] However, since it is difficult to maintain the membrane structure using only sulfide compounds, solid electrolyte membranes can be manufactured by mixing binders.
[0065] Here, as an adhesive, it is preferable to have excellent adhesion to the sulfide-based compound, no decrease in ionic conductivity, and excellent flexibility. Furthermore, it should be easily peelable from release films commonly used in the manufacture of solid electrolyte membranes.
[0066] Examples include polyvinylidene fluoride (PVDF), PVDF-co-HFP copolymer, polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or multiple copolymers thereof. One of these can be used alone or in mixtures of two or more.
[0067] This type of solid electrolyte membrane can be manufactured by coating a slurry, including sulfide compounds, binders and solvents, onto a release film and then removing the solvent.
[0068] Furthermore, the solid electrolyte membrane may, as needed, include conductive materials, auxiliary binders, etc.
[0069] Conductive materials are used to impart conductivity so that electrons can move along with ions. Their types are unrestricted as long as they are materials that do not undergo unnecessary chemical reactions and possess electronic conductivity. Examples include graphite, carbon black, acetylene black, Ketjen black, furnace black, lamp black, thermal cracking black, carbon fiber, carbon nanotubes, graphene, copper, aluminum, nickel, gold, silver, and conductive polymers.
[0070] In the solid electrolyte membrane, the content of the sulfide-based solid electrolyte compound can be 80-99.9% by weight, for example 80% by weight, 80.5% by weight, 81% by weight, 81.5% by weight, 82% by weight, 82.5% by weight, 83% by weight, 83.5% by weight, 84% by weight, 84.5% by weight, 85% by weight, 85.5% by weight, 86% by weight, 86.5% by weight, 87% by weight, 87.5% by weight, 88% by weight, 88.5% by weight, and 89% by weight. 89.5% by weight, 90% by weight, 90.5% by weight, 91% by weight, 91.5% by weight, 92% by weight, 92.5% by weight, 93% by weight, 93.5% by weight, 94% by weight, 94.5% by weight, 95% by weight, 95.5% by weight, 96% by weight, 96.5% by weight, 97% by weight, 97.5% by weight, 98% by weight, 98.5% by weight, 99% by weight, 99.5% by weight, 99.9% by weight, or a range between two of these values, but not limited to these.
[0071] Here, the thickness of the solid electrolyte membrane is not limited and can range from 5 to 300 mm. For example, 5 10 15 20 25 30 35 40 45 50 55 60 65 70 75 80 85 90 95 100 105 110 115 120 125 130 135 140 145 150 155 160 165 170 175 180 185 190 195 200 205 210 215 220 225 230 235 240 245 250 255 260 265 270 275 280 285 290 295 300 Or the range between two of these values.
[0072] On the other hand, the solid electrolyte membrane may have a free-standing characteristic that allows it to be used without a separate support, but is not limited thereto.
[0073] Lithium secondary batteries According to another aspect of this specification, a lithium secondary battery having the aforementioned solid electrolyte membrane can be provided.
[0074] The solid electrolyte membrane can be disposed as a separate layer (solid electrolyte layer) between the positive and negative electrodes. Furthermore, the solid electrolyte can be independently and partially included within the positive electrode active material layer of the positive electrode, or the solid electrolyte can be independently and partially included within the negative electrode active material layer of the negative electrode.
[0075] That is, the lithium secondary battery may specifically include a positive electrode, a negative electrode positioned opposite the positive electrode, and a solid electrolyte membrane between the positive electrode and the negative electrode. Here, since the solid electrolyte membrane is the same as that described above, its specific description is omitted for convenience, and only the remaining components not described are specifically described below.
[0076] The lithium secondary battery may optionally further include a battery container housing an electrode assembly comprising the positive electrode, the negative electrode, and the solid electrolyte membrane, and a sealing component for sealing the battery container.
[0077] The positive electrode may include a positive current collector and a layer of positive active material located on the positive current collector.
[0078] As long as the positive current collector does not cause chemical changes to the battery and is conductive, it is not particularly limited. For example, it can be made of stainless steel, aluminum, nickel, titanium, sintered carbon, or surface-treated aluminum or stainless steel with carbon, nickel, titanium, silver, etc. Furthermore, the positive current collector typically has a thickness of 3 μm to 500 μm, and fine irregularities can be formed on its surface to improve the adhesion of the positive electrode active material. For example, it can be used in various forms such as thin films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.
[0079] As the positive electrode active material, compounds capable of reversible lithium insertion / extraction can be used. Examples include, but are not limited to, cobalt oxide (LCO), nickel oxide (LNO), manganese oxide (LMO), nickel-cobalt-manganese oxide (NCM), nickel-cobalt-aluminum oxide (NCA), iron phosphate (LFP), and compounds doped with and / or coated with these.
[0080] The positive electrode active material layer can be manufactured by coating the positive electrode current collector with a positive electrode slurry composition that, together with the positive electrode active material, selectively includes conductive materials and binders as needed.
[0081] At this point, the positive electrode active material can be contained in an amount of 80% to 99% by weight, more specifically 85% to 98.5% by weight, relative to the total weight of the positive electrode active material layer. Excellent capacity characteristics can be exhibited when contained within this range, but it is not necessarily limited thereto.
[0082] The conductive material is used to impart conductivity to the electrodes. In the constructed battery, any material that exhibits electronic conductivity without causing a chemical change can be used without particular restriction. Specific examples include graphite such as natural or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking black, and carbon fiber; metal powders or fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives. One of these materials can be used alone or in combination of two or more. The conductive material can be contained in an amount from 0.1% to 15% by weight relative to the total weight of the positive electrode active material layer.
[0083] The binder enhances the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), PVDF-co-HFP, polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof. One of these binders may be used alone or in combination of two or more. The binder may be contained in an amount from 0.1% to 15% by weight relative to the total weight of the positive electrode active material layer.
[0084] The positive electrode can be prepared according to conventional positive electrode preparation methods. Specifically, it can be prepared by coating a positive electrode slurry composition, which is prepared by dissolving or dispersing positive electrode active material, binder and conductive material in a solvent, onto a positive electrode current collector, followed by drying and rolling.
[0085] The solvent can be any solvent commonly used in this technical field, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, etc., and can be used alone or in combination with two or more. The amount of solvent used should be sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, taking into account the coating thickness and preparation yield of the slurry, and to achieve a viscosity that provides excellent uniformity of thickness during subsequent coating for the preparation of the positive electrode.
[0086] In another embodiment, the positive electrode can also be prepared by casting the positive electrode slurry composition onto a separate support, and then pressing the membrane layer obtained by peeling it off from the support onto the positive electrode current collector.
[0087] The negative electrode may include a negative electrode current collector and a layer of negative electrode active material located on the negative electrode current collector.
[0088] The negative electrode current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery. For example, it can be made of copper, stainless steel, aluminum, nickel, titanium, sintered carbon, materials with surface treatments of copper or stainless steel using carbon, nickel, titanium, silver, etc., or aluminum-cadmium alloys. Furthermore, the negative electrode current collector typically has a thickness of 3 μm to 500 μm, and similarly to the positive electrode current collector, fine irregularities can be formed on its surface to enhance the adhesion of the negative electrode active material. For example, it can be used in various forms such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.
[0089] The negative electrode active material layer can be prepared by coating the negative electrode current collector with a negative electrode slurry composition that includes a conductive material together with the negative electrode active material and, if necessary, a binder.
[0090] As the negative electrode active material, compounds capable of reversible lithium insertion and extraction can be used. Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fibers, and amorphous carbon; metallic compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; metal oxides capable of doping and dedoping lithium, such as SiOβ (0 < β < 2), SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the aforementioned metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites. Any one or a mixture of two or more of these can be used. Furthermore, a thin film of metallic lithium can also be used as the negative electrode active material. Additionally, all types of carbon materials, including low-crystallinity carbon and high-crystallinity carbon, can be used. As low-crystallinity carbon, soft carbon and hard carbon are representative examples. As highly crystalline carbon, amorphous, plate-like, flake-like, spherical, or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature sintered carbons such as petroleum or coal tar pitchdered cokes are representative examples.
[0091] The negative electrode active material may be contained in 80% to 99% by weight based on the total weight of the negative electrode active material layer.
[0092] The binder, as a component that assists in the bonding between the conductive material, the active material and the current collector, is typically added at a rate of 0.1% to 10% by weight, based on the total weight of the negative electrode active material layer.
[0093] Examples of such adhesives include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.
[0094] The conductive material is a component used to further improve the conductivity of the negative electrode active material, and can be added at a rate of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. This conductive material is not particularly limited as long as it is conductive without causing a chemical change in the battery. For example, graphite such as natural or artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal cracking black; conductive fibers such as carbon fiber or metal fiber; metal powders such as fluorinated carbon, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0095] In one embodiment, the negative electrode active material layer can be prepared by coating a negative electrode slurry composition, which is prepared by dissolving or dispersing the negative electrode active material and a binder and conductive material in a solvent, onto the negative electrode current collector and then drying it, or by casting the negative electrode slurry composition onto a separate support and then pressing the film layer obtained by peeling it off from the support onto the negative electrode current collector.
[0096] As described above, lithium secondary batteries, including those with solid electrolyte membranes according to this specification, do not experience overvoltage increases and exhibit stable cycle characteristics, and therefore can be used in portable devices such as mobile phones, laptops, and digital cameras, as well as in electric vehicles such as hybrid electric vehicles (HEVs).
[0097] The shape of the lithium secondary battery according to the present invention is not particularly limited, but it can be cylindrical, square, pouch-shaped, or coin-shaped, etc. Furthermore, the lithium secondary battery can be used not only as a battery cell for powering small devices, but also preferably as a unit battery in medium to large-sized battery modules containing multiple battery cells.
[0098] According to another aspect of the present invention, a battery module comprising the lithium secondary battery as a unit and / or a battery pack comprising the same can be provided.
[0099] The battery module or battery pack can be used as a power tool; an electric vehicle including electric vehicles (EVs), hybrid electric vehicles and plug-in hybrid electric vehicles (PHEVs); or a power source for medium to large-sized equipment in a power storage system.
[0100] The following examples will provide a more detailed description of the described matters. However, these examples are for illustrative purposes only, and the scope of this specification should not be construed as being limited to these examples.
[0101] Manufacturing Example 1. Manufacturing of Sulfide Compounds Comparative Example 1 In a drying chamber (DP-60℃), lithium precursor Li2S, phosphorus precursor P2S5, and chlorine precursor LiCl are reacted to obtain Li with the desired composition. 5.7 PS 4.7 Cl 1.3 Weigh and mix according to stoichiometric ratio.
[0102] The mixture was placed in a crucible containing Al2O3 and then fired. To suppress the reaction with the gas present inside the firing furnace, N2 gas was passed through as an inactive gas and the temperature was raised to a maximum of 570°C for heat treatment, thereby firing to produce the sulfide compound of Comparative Example 1.
[0103] Comparative Example 2 In addition to processing lithium precursor Li2S, phosphorus precursor P2S5, chlorine precursor LiCl, and bromine precursor LiBr in a drying chamber (DP-60℃) to obtain Li with the desired composition. 6.15 PS 4.7 Cl 1.3 Br 0.45 The sulfide compounds were prepared in the same manner as in Comparative Example 1, except that they were weighed according to stoichiometric ratios.
[0104] Example 1 In addition to processing lithium precursor Li2S, phosphorus precursor P2S5, chlorine precursor LiCl, and bromine precursor LiBr in a drying chamber (DP-60℃) to obtain Li with the desired composition. 5.775 PS 4.7 Cl 1.3 Br 0.075 Except for weighing, sulfide compounds were prepared in the same manner as in Comparative Example 1.
[0105] Example 2 In addition to processing lithium precursor Li2S, phosphorus precursor P2S5, chlorine precursor LiCl, and bromine precursor LiBr in a drying chamber (DP-60℃) to obtain Li with the desired composition. 5.85 PS 4.7 Cl 1.3 Br 0.15 Except for weighing, sulfide compounds were prepared in the same manner as in Comparative Example 1.
[0106] Experimental Example 1. Characteristic Analysis of Sulfide Compounds The composition, ionic conductivity before and after atmospheric exposure, lattice parameter, and intensity ratio I(200) / I(220) of the (200) plane of the LiCl crystal phase and the (220) plane of the sulfide-germanium sulfide-type crystal phase were determined according to Manufacturing Example 1 and are shown in Table 1 below.
[0107] XRD analysis was performed using a Bruker D8 Advance diffractometer with Cu-Kα radiation (1.540598 Å), and the results are shown below. Figure 1 middle.
[0108] To evaluate atmospheric stability, air with a controlled dew point (DP-40℃) was circulated through a sulfide-based compound at room temperature. The amount of hydrogen sulfide produced was measured using a hydrogen sulfide sensor and displayed. Figure 2 The ionic conductivity of the sulfide compounds was measured before and after the evaluation.
[0109] [Table 1]
[0110] Referring to Table 1, Comparative Example 1 (which did not contain bromine) and Comparative Example 2 (which had an excessively high bromine ratio) exhibited lower ionic conductivity than the examples. This difference became even more pronounced after atmospheric stability evaluation. In particular, Comparative Example 2, despite containing residual LiCl, showed a sharp decrease in ionic conductivity after atmospheric exposure. Figure 1 As shown in Table 1, in the sulfide compounds of Comparative Example 2, Example 1 and Example 2, it can be confirmed that LiCl remains due to excess LiBr.
[0111] refer to Figure 2 Due to the influence of residual LiCl, the amount of hydrogen sulfide produced in Example 1 was reduced compared to Comparative Example 1.
[0112] Manufacturing Example 2. Manufacturing of Solid Electrolyte Membrane and Lithium Secondary Battery (Symmetric Cell) A pressure battery was manufactured by applying a uniaxial pressure of 200 MPa to 200 mg of the sulfide compound used in the comparative examples and embodiments. At this time, Li metal was inserted into both ends of the solid electrolyte to create a symmetrical lithium secondary battery with a Li / sulfide compound / Li electrode structure.
[0113] Experimental Example 2. Evaluation of the electrochemical characteristics of a lithium secondary battery (symmetric battery) The lithium-ion secondary battery (symmetric battery) manufactured in Example 2 was evaluated using a Toyo TOSCAT-3100 instrument. A current of 0.25 mA per unit area was applied for 300 cycles. Stripping and plating were repeated for 1 hour each cycle to evaluate the electrochemical stability of the solid electrolyte, and the results are shown below. Figure 3 middle.
[0114] Typically, due to the narrow potential window of solid electrolytes, decomposition reactions of the solid electrolyte occur at the interface between the lithium electrode and the solid electrolyte. However, reference Figure 3 In the symmetric cell of Example 1 containing LiCl with a wide and stable potential window relative to the solid electrolyte, the interfacial decomposition reaction was suppressed, the overvoltage on the y-axis did not increase, and stable cycling behavior was observed.
[0115] The embodiments of the present invention have been described above. However, those skilled in the art can make various modifications and alterations to the present invention by adding, changing, deleting, or supplementing constituent elements without departing from the spirit of the present invention as described in the claims, and these modifications and alterations should also be considered to be included within the scope of the present invention.
Claims
1. A sulfide-based solid electrolyte compound, characterized in that, The sulfide-based solid electrolyte compound comprises an Argyrodite-type crystal phase, and at least a portion of its surface includes a LiX crystal phase. X is at least one selected from the group consisting of F, Cl, Br and I.
2. The sulfide-based solid electrolyte compound according to claim 1, characterized in that, The peak intensity ratio I(200) / I(220) of the (220) plane of the sulfosilver germanite-type crystal structure and the (200) plane of the LiX crystal phase is less than 0.
30.
3. The sulfide-based solid electrolyte compound according to claim 1, characterized in that, In the crystal phase of the sulfogermanium ore-type crystal structure, the molar ratio of lithium (Li) to phosphorus (P) is greater than 5.7 and less than 6.
15.
4. The sulfide-based solid electrolyte compound according to claim 1, characterized in that, In the crystal phase of the sulfosilver-germanium ore type crystal structure, the molar ratio of sulfur (S) to phosphorus (P) is 4.00~6.
00.
5. The sulfide-based solid electrolyte compound according to claim 1, characterized in that, The crystal phase of the sulfosilver-germanium ore-type crystal structure includes two or more halogen elements.
6. The sulfide-based solid electrolyte compound according to claim 1, characterized in that, In the crystal phase of the sulfogermanium ore-type crystal structure, the molar ratio of halogen (X) to phosphorus (P) is 1.00~2.
00.
7. The sulfide-based solid electrolyte compound according to claim 6, characterized in that, In the crystal phase of the sulfogermanium-type crystal structure, the molar ratio (Li+X) / P of the sum of lithium (Li) and halogen (X) elements relative to phosphorus (P) is greater than 7.
00.
8. The sulfide-based solid electrolyte compound according to claim 1, characterized in that, The crystal phase of the silver-germanium sulfide-type crystal structure is represented by the following chemical formula 1: [Chemical Formula 1] Li 7-x+y PS 6-x Cl x Br y In the aforementioned chemical formula 1, 1 ≤ x ≤ 1.6, 0 <y≤0.4。 9. The sulfide-based solid electrolyte compound according to claim 8, characterized in that, The peak intensity ratio I(200) / I(220) of the (220) facet of the sulfosilver germanite-type crystal structure and the (200) facet of the LiCl crystal phase is less than 0.
30.
10. The sulfide-based solid electrolyte compound according to claim 1, characterized in that, The crystal phase of the sulfosilver-germanium type crystal structure has a lattice constant greater than 9.439 Å and less than 9.645 Å.
11. The sulfide-based solid electrolyte compound according to claim 1, characterized in that, The sulfide-based solid electrolyte compound is prepared by mixing lithium sulfide (Li₂S) powder, phosphorus pentasulfide (P₂S₅) powder, lithium chloride (LiCl) powder, and lithium bromide (LiBr) powder, and then heating the mixture at 350°C under an inert atmosphere. Firing at 600℃, or at 350℃ in an atmosphere containing hydrogen sulfide gas. It is obtained by firing at 650℃.
12. The sulfide-based solid electrolyte compound according to claim 11, characterized in that, The content of the lithium chloride (LiCl) powder is higher than the content of the lithium bromide (LiBr) powder.
13. A solid electrolyte membrane, characterized in that, Includes sulfide-based solid electrolyte compounds according to any one of claims 1 to 12.
14. A lithium secondary battery, characterized in that, Includes the solid electrolyte membrane according to claim 13.
